FERULA L. ТУРКУМИ ТУРЛАРИНИНГ ҒАРБИЙ ПОМИР-ОЛОЙ ҲУДУДИДА ТАРҚАЛИШИ ВА ГАТ ХАРИТАСИ - Джуманиёзова, Ф.С. (SCIENCE and SOCIETY, 2020)
The current state of the species of the Ferula penninervis Regel et Schmalh., Ferula ovina (Boiss.) Boiss., Ferula dshizakensis Korovin, Ferula angrenii Korovin, Ferula kuhistanica Korovin, Ferula kokanica Regel et Schmalh., Ferula samarkandica Korovin, Ferula helenae Rakhmankulov et Melibaev, Ferula diversivittata Regel et Schmalh., Ferula foetida (Bunge) Regel. Ferula ovina (Boiss.) Boiss., Ferula dshizakensis Korovin, Ferula angrenii Korovin, Ferula kuhistanica Korovin, Ferula kokanica Regel et Schmalh., Ferula samarkandica Korovin, Ferula helenae Rakhmankulov et Melibaev, Ferula diversivittata Regel et Schmalh., Ferula foetida (Bunge) Regel., population in Western Pamir-Alai has been determined, the range has been specified and a GIS map has been compiled.
Keywords: GIS; Ferula; species; population; range; anthropogen; introduction; mapping